A preparation method and application of a self-cleaning membrane using a two-dimensional layer structure

By preparing a self-cleaning film of two-dimensional sheet layer structure, using the hydrothermal reaction in situ conversion technology of conductive base film and LDH film, the problems of insufficient selection performance and contamination of flux in the existing two-dimensional MOFs film are solved, and efficient removal is achieved Pollutants and low-cost mass production.

CN117160259BActive Publication Date: 2024-12-24NANJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311319240.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2024-12-24
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

The existing two-dimensional MOFs membranes have insufficient selection performance when removing contaminants. The membrane flux is affected by membrane contamination, and the construction of expensive ligands leads to low yield and high cost, making it difficult to produce on a large scale.

Method used

The preparation method of a two-dimensional sheet-structure self-cleaning film is adopted. The 2D MOFs film is prepared by the preparation of conductive base film and LDH film, combined with hydrothermal reaction in situ conversion, and the pollutants are removed using negative charge and pore size, and vacuum pumping is used. Filtration and electrocatalytic self-cleaning technology.

Benefits of technology

It has achieved high selectivity and high water flux pollution removal, strong anti-pollution ability, can remove most membrane pollution during the self-cleaning process of power-on, high flux recovery rate, low cost, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117160259B_ABST
    Figure CN117160259B_ABST
Patent Text Reader

Abstract

The present application discloses a method for preparing a self-cleaning membrane using a two-dimensional layered structure and its application. A two-dimensional layered metal hydroxide (LDH) is loaded on a substrate membrane (PVDF) and a polyethersulfone (PES), and is in situ converted into a two-dimensional metal organic framework under hydrothermal conditions. The LDH membrane is in situ converted into a two-dimensional MOFs membrane. Compared with the existing reported methods, the use of expensive organic ligands is avoided, the yield is greatly improved, and it is suitable for mass production. The constructed two-dimensional MOFs membrane has excellent hydrophilic properties and has a hydrophilicity of up to 622.7 L·m ‑2 ·h ‑1 bar ‑1 The water flux is high, it has excellent retention rate for new pollutants such as antibiotics in wastewater, and it also has self-cleaning properties, effectively controlling membrane fouling; it is a method for removing trace new pollutants such as drugs and personal care products PPCPs in wastewater, aiming to develop a highly selective, high-throughput self-cleaning nanofiltration membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of self-cleaning nanofiltration membranes, and in particular to a preparation method and application of a self-cleaning membrane using a two-dimensional layer structure. Background Art

[0002] Faced with the current crisis of severe water shortage on the earth, sewage and wastewater regeneration is an effective way to sustainably recycle water resources. Therefore, it is of great significance to quickly and effectively remove new pollutants such as PPCP from water.

[0003] Membrane separation technology has the advantages of low energy consumption, good selectivity, and strong adaptability. It has been widely used in separation processes, including seawater desalination, sewage treatment, pure water preparation, food processing, as well as medicine, biology, environmental protection and many other fields. Two-dimensional (2D) materials, such as graphene oxide (GO), metal carbide (MXene), MoS2, etc., have been widely used to prepare membrane materials. Among them, two-dimensional MOF nanosheets are used as new materials for making nanofiltration membranes because they have abundant and regular in-plane nanopores, which are not available in the current advanced graphene-based membranes. In addition, 2D MOFs membranes are superior to most 2D membranes in terms of water / ion selectivity. The surface charge of the membrane can be changed by adjusting the organic ligands to selectively separate pollutants. Although the 2D structure membrane is stacked layer by layer in a special way and the membrane layer is relatively thin, it is slightly insufficient in terms of selectivity. In addition, during the long-term operation of 2D MOFs membranes to remove pollutants, membrane contamination seriously affects the membrane flux. Existing two-dimensional MOFs are usually constructed with expensive ligands and need to be ultrasonically stripped, resulting in low yields, high costs, and difficulty in large-scale production. Based on this, there is an urgent need to develop a self-cleaning separation membrane that has both high selectivity and high water flux and can be mass-produced. Summary of the invention

[0004] Technical issues solved:

[0005] The technical problem that needs to be solved in this application is that the 2D structure membrane has a slight deficiency in selectivity performance, membrane contamination seriously affects membrane flux, and existing two-dimensional MOFs are usually constructed from expensive ligands and require ultrasonic exfoliation, resulting in very low yield, high cost, and difficulty in large-scale production. The present application provides a method for preparing a self-cleaning membrane using a two-dimensional lamellar structure and its application, which has high selectivity and high flux.

[0006] Technical solution:

[0007] A method for preparing a self-cleaning membrane using a two-dimensional sheet structure, wherein the specific process conditions are:

[0008] Step 1: Preparation of conductive substrate membrane: dissolve organic polymer and porogen in 25-75 ml N, N-dimethylformamide DMF at a mass ratio of 7.54:1-3, fully stir for 12-24 hours, add 50% conductive graphite powder based on the organic polymer molecular weight and fully stir for 12-24 hours at 60-70°C to obtain a casting solution; let stand for 12-24 hours to degas; cast the casting solution on the surface of non-woven fabric using a coating machine, and place it in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a membrane thickness of 200-400 μm;

[0009] Step 2, preparation of LDH: Solution A is prepared by dissolving divalent nitrate and trivalent nitrate in 30-60 mL of deionized water; then sodium hydroxide and sodium carbonate are dissolved in 30-60 mL of deionized water to prepare solution B; solution A and solution B are mixed and vigorously stirred for 1-2 hours, transferred to a stainless steel Teflon-lined autoclave for co-precipitation and heated at 80-120°C for hydrothermal reaction for 24-48 hours, cooled and fully washed with deionized water and ethanol, and the obtained LDH solid corresponding to the metal is then dried in a vacuum at 60-70°C for 12-18 hours to prepare LDH nanosheets; the molar ratio of divalent nitrate, trivalent nitrate, sodium hydroxide and sodium carbonate is (1-2):(1-2):6.4:2.66;

[0010] The third step is to prepare the LDH membrane: suspend the LDH nanosheets in an ethanol solution, disperse them evenly by ultrasonication for 30-60 minutes, vacuum filter them on a PVDF conductive graphite substrate membrane using an ultrafiltration cup, and then dry them at 30-50°C for 6-12 hours to obtain the LDH membrane;

[0011] The fourth step is the preparation of 2D MOFs membrane: the LDH membrane is placed in an anhydrous ethanol solution containing organic ligands, and a 2D MOFs membrane is obtained by in-situ conversion on the membrane at 120-160°C for 24-48 hours. After cooling, the 2D MOFs membrane is washed with ethanol several times, and then placed in a vacuum dryer at 60-70°C for 12-18 hours to obtain a self-cleaning membrane using a two-dimensional lamellar structure.

[0012] As a preferred technical solution of the present application: the organic polymer in the first step is polyvinylidene fluoride PVDF or polyether sulfone PES.

[0013] As a preferred technical solution of the present application: the porogen in the first step is polyvinyl pyrrolidone PVP and / or polyethylene glycol PEG.

[0014] As a preferred technical solution of the present application: the divalent nitrate in the second step is one or more of cobalt nitrate Co(NO3)2·6H2O, zinc nitrate Zn(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and magnesium nitrate Mg(NO3)2·6H2O.

[0015] As a preferred technical solution of the present application: in the second step, the trivalent nitrate is iron nitrate Fe(NO3)3·9H2O and / or aluminum nitrate Al(NO3)3·9H2O.

[0016] As a preferred technical solution of the present application: in the fourth step, the organic ligand is one or more of terephthalic acid, 2,5-dihydroxyterephthalic acid, and 2-aminoterephthalic acid; the method for preparing the anhydrous ethanol solution containing the organic ligand is to dissolve 50-150 mg of the organic ligand in 60 mL of anhydrous ethanol solution and ultrasonicate for 30 minutes.

[0017] As a preferred technical solution of the present application: in the third step, the amount of LDH nanosheets used is 25-75 mg, the amount of ethanol solution used is 200 mL, the thickness of the functional layer of the filtered membrane is 5 μm, and the thickness of the functional layer of the 2D MOFs membrane after in-situ conversion by hydrothermal reaction in the fourth step is 15.6 μm.

[0018] The present application also discloses the use of a two-dimensional lamellar structure self-cleaning membrane obtained by the above-mentioned preparation method in high-throughput removal of PPCPs pollutants in sewage, wherein the two-dimensional lamellar structure self-cleaning membrane is used as an anode to degrade and remove simulated pollutants on the membrane in situ under an external electric field by vacuum filtration, and the pore size of the two-dimensional lamellar structure self-cleaning membrane is 1-2nm.

[0019] As a preferred technical solution of the present application: the concentration of the simulated pollutant is 200 μg / L.

[0020] As a preferred technical solution of the present application: the vacuum filtration is performed at a pressure of 0.1-5 bar.

[0021] Beneficial effects:

[0022] The preparation method and application of a two-dimensional sheet structure self-cleaning membrane described in the present application adopt the above technical solution and have the following technical effects compared with the prior art:

[0023] 1. The self-cleaning membrane using a two-dimensional sheet structure of the present invention has both high selectivity and high water flux and can be mass-produced;

[0024] 2. The removal effects of the two-dimensional sheet structure self-cleaning membrane of the present invention on the negatively charged antibiotics TC, NOR, and SMX are 98.2%, 86.2%, and 83.1%, respectively;

[0025] 3. The water flux of the two-dimensional sheet structure self-cleaning membrane of the present invention is 1-2 orders of magnitude higher than that of the two-dimensional nanofiltration membrane reported previously;

[0026] 4. The two-dimensional sheet structure self-cleaning membrane of the present invention has a high anti-pollution ability and an excellent self-cleaning effect, and can remove most of the membrane pollution during the powered self-cleaning process. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 (a) is a SEM image of CoFe-LDH of the present application, (b) is a TEM image of CoFe-LDH, c is a SEM image of CoFe-MOFs, and d is a TEM image of CoFe-MOFs;

[0028] Figure 2 (ac) are test diagrams of the bending performance of the CoFe-MOFs / M film of the present application, (de) is a cross-sectional view of the CoFe-LDH-M film, (fg) is an EDS spectrum of the cross-sectional view of the CoFe-LDH-M film, (hi) is a cross-sectional view of the CoFe-MOFs-M film, and (jk) is an EDS spectrum of the cross-sectional view of the CoFe-MOFs-M film;

[0029] Figure 3 This is the retention performance diagram of antibiotics by 2D-MOFs / M, CoFe-LDH / M and PVDF / M in this application;

[0030] Figure 4 This is a bar graph of water flux of 2D-MOFs / M, CoFe-LDH / M and PVDF / M membranes in this application;

[0031] Figure 5 This is a performance comparison chart of CoFe-MOFs / M and other two-dimensional membranes in this application;

[0032] Figure 6 (a) is the AFM image of CoFe-LDH of the present application, and (b) CoFe-MOFs nanosheets;

[0033] Figure 7 The middle left picture is the membrane anti-fouling diagram of PVDF, CoFe-LDH / M, and CoFe-MOFs / M in this application, and the right picture is its membrane resistance diagram;

[0034] Figure 8 Diagram of the self-cleaning cycle of CoFe-MOFs / M membrane fouling for this application.

[0035] Fig. 9 This is a diagram showing the removal effect of CoFe-MOFs / M membrane on different antibiotics in this application. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:

[0037] Preparation of conductive substrate membrane: dissolving organic polymer and porogen in 25-75 ml N,N-dimethylformamide DMF at a mass ratio of 2.51-7.54:1, fully stirring for 12-24 hours, adding 50% conductive graphite powder based on the organic polymer molecular weight and fully stirring at 60-70°C for 12-24 hours to obtain a casting solution; standing for 12-24 hours to degas; casting the casting solution on the surface of a non-woven fabric using a coating machine, placing it in deionized water for phase inversion treatment, and obtaining a PVDF conductive graphite substrate membrane with a membrane thickness of 200-400 μm; the organic polymer is polyvinylidene fluoride PVDF or polyether sulfone PES; the porogen is polyvinyl pyrrolidone PVP and / or polyethylene glycol PEG.

[0038] Embodiment 1:

[0039] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a CoFe-MOFs membrane, and CoFe-LDH is synthesized by coprecipitation and hydrothermal method using cobalt nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF membrane, and then in situ converted into a 2D MOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0040] (1) Co(NO3)2·6H2O (9 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 1:1.

[0041] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0042] (3) Mix the above two solutions and stir vigorously for 1 h.

[0043] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave for co-precipitation and heated at 80° C. for 48 h.

[0044] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0045] (6) CoFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0046] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0047] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0048] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0049] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0050] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0051] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0052] Example 2

[0053] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a CoFe-MOFs membrane, and CoFe-LDH is synthesized by coprecipitation and hydrothermal method using cobalt nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF membrane, and then in situ converted into a 2D MOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0054] (1) Co(NO3)2·6H2O (9 mmol) and Fe(NO3)3·9H2O (18 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 1:2.

[0055] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0056] (3) Mix the above two solutions and stir vigorously for 1 h.

[0057] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0058] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0059] (6) CoFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0060] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0061] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0062] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0063] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0064] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0065] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0066] Example 3

[0067] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a CoFe-MOFs membrane, and CoFe-LDH is synthesized by coprecipitation and hydrothermal method using cobalt nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF membrane, and then in situ converted into a 2D MOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0068] (1) Co(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0069] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0070] (3) Mix the above two solutions and stir vigorously for 1 h.

[0071] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0072] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0073] (6) CoFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0074] (7) The LDH solution was pumped onto the PVDF conductive substrate membrane by vacuum filtration and dried in an oven at 40° C. to constant weight.

[0075] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0076] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0077] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0078] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0079] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0080] Example 4

[0081] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a CoFe-MOFs membrane, and CoFe-LDH is synthesized by coprecipitation and hydrothermal method using cobalt nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF membrane, and then in situ converted into a 2D MOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0082] (1) Co(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0083] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0084] (3) Mix the above two solutions and stir vigorously for 1 h.

[0085] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0086] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0087] (6) CoFe-LDH (50 mg) was added to ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0088] (7) The LDH solution was pumped onto the PVDF conductive substrate membrane by vacuum filtration and dried in an oven at 40° C. to constant weight.

[0089] (8) Dissolve 100 mg of terephthalic acid in 60 mL of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0090] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0091] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0092] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0093] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0094] Example 5

[0095] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a CoFe-MOFs membrane, and CoFe-LDH is synthesized by coprecipitation and hydrothermal method using cobalt nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF membrane, and then in situ converted into a 2D MOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0096] (1) Co(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0097] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0098] (3) Mix the above two solutions and stir vigorously for 1 h.

[0099] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0100] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0101] (6) CoFe-LDH (25 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0102] (7) The LDH solution was pumped onto the PVDF conductive substrate membrane by vacuum filtration and dried in an oven at 40° C. to constant weight.

[0103] (8) Dissolve 50 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0104] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0105] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0106] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0107] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0108] Example 6

[0109] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a CoFe-MOFs membrane, and CoFe-LDH is synthesized by coprecipitation and hydrothermal method using cobalt nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF membrane, and then in situ converted into a 2D MOFs membrane by reacting with a 2,5-dihydroxyterephthalic acid ligand. The specific synthesis route is as follows:

[0110] (1) Co(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0111] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0112] (3) Mix the above two solutions and stir vigorously for 1 h.

[0113] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0114] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0115] (6) CoFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0116] (7) The LDH solution was pumped onto the PVDF conductive substrate membrane by vacuum filtration and dried in an oven at 40° C. to constant weight.

[0117] (8) Dissolve 150 mg of 2,5-dihydroxyterephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0118] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0119] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0120] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0121] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0122] Example 7

[0123] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a CoFe-MOFs membrane, and CoFe-LDH is synthesized by coprecipitation and hydrothermal method using cobalt nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF membrane, and then in situ converted into a 2D MOFs membrane by reacting with a 2-aminoterephthalic acid ligand. The specific synthesis route is as follows:

[0124] (1) Co(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0125] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0126] (3) Mix the above two solutions and stir vigorously for 1 h.

[0127] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0128] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0129] (6) CoFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0130] (7) The LDH solution was pumped onto the PVDF conductive substrate membrane by vacuum filtration and dried in an oven at 40° C. to constant weight.

[0131] (8) Dissolve 150 mg of 2-aminoterephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0132] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0133] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0134] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0135] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0136] Embodiment 8:

[0137] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a MgAl-MOFs membrane, and MgAl-LDH is synthesized by coprecipitation and hydrothermal method using magnesium nitrate and aluminum nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF conductive graphite substrate membrane, and then in-situ converted into a 2DMOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0138] (1) Mg(NO3)2·6H2O (18 mmol) and Al(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0139] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0140] (3) Mix the above two solutions and stir vigorously for 1 h.

[0141] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0142] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0143] (6) MgAl-LDH (75 mg) was added to ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0144] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0145] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0146] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0147] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0148] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0149] The preparation of the PVDF conductive graphite substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0150] Embodiment 9:

[0151] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a MgFe-MOFs membrane, and MgFe-LDH is synthesized by coprecipitation and hydrothermal method using magnesium nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF conductive graphite substrate membrane, and then in-situ converted into a 2DMOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0152] (1) Mg(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0153] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0154] (3) Mix the above two solutions and stir vigorously for 1 h.

[0155] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0156] (5) After cooling, the MgFe-LDH solid was thoroughly washed with deionized water and ethanol, and dried in an oven at 60°C for 12 hours.

[0157] (6) MgFe-LDH (75 mg) was added to ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0158] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0159] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0160] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0161] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0162] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0163] The preparation of the PVDF conductive graphite substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0164] Embodiment 10:

[0165] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a NiFe-MOFs membrane, and NiFe-LDH is synthesized by coprecipitation and hydrothermal method using nickel nitrate and ferric nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF conductive graphite substrate membrane, and then in-situ converted into a 2DMOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0166] (1) Ni(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0167] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0168] (3) Mix the above two solutions and stir vigorously for 1 h.

[0169] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0170] (5) After cooling, the solid NiFe-LDH was thoroughly washed with deionized water and ethanol, and dried in an oven at 60°C for 12 hours.

[0171] (6) NiFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0172] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0173] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0174] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0175] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0176] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0177] The preparation of the PVDF conductive substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0178] Embodiment 11:

[0179] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a ZnFe-MOFs membrane, zinc nitrate and ferric nitrate are used with sodium hydroxide and sodium carbonate, and ZnFe-LDH is synthesized by coprecipitation and hydrothermal method, and then loaded on a PVDF conductive graphite substrate membrane, and then in situ converted into a 2DMOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0180] (1) Zn(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0181] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0182] (3) Mix the above two solutions and stir vigorously for 1 h.

[0183] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0184] (5) After cooling, the solid ZnFe-LDH was thoroughly washed with deionized water and ethanol, and dried in an oven at 60°C for 12 hours.

[0185] (6) ZnFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0186] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0187] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0188] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0189] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0190] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0191] The preparation of the PVDF conductive graphite substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0192] Embodiment 12:

[0193] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, using the two-dimensional lamellar structure self-cleaning membrane as a CoAl-MOFs membrane, using cobalt nitrate and aluminum nitrate with sodium hydroxide and sodium carbonate, synthesizing CoAl-LDH by coprecipitation and hydrothermal method, and then loading it on a PVDF conductive graphite substrate membrane, and then in-situ converting it into a 2DMOFs membrane through terephthalic acid ligands. The specific synthesis route is as follows:

[0194] (1) Co(NO3)2·6H2O (18 mmol) and Al(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0195] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0196] (3) Mix the above two solutions and stir vigorously for 1 h.

[0197] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0198] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoAl-LDH solid was placed in an oven at 60°C and dried for 12 hours.

[0199] (6) CoAl-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0200] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0201] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0202] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0203] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0204] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0205] The preparation of the PVDF conductive graphite substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0206] Embodiment 13:

[0207] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a NiAl-MOFs membrane, and NiAl-LDH is synthesized by coprecipitation and hydrothermal method using nickel nitrate and aluminum nitrate, sodium hydroxide and sodium carbonate, and then loaded on a PVDF conductive graphite substrate membrane, and then in situ converted into a 2DMOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0208] (1) Ni(NO3)2·6H2O (18 mmol) and Al(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0209] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0210] (3) Mix the above two solutions and stir vigorously for 1 h.

[0211] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0212] (5) After cooling, the solid NiAl-LDH was thoroughly washed with deionized water and ethanol, and dried in an oven at 60°C for 12 hours.

[0213] (6) NiAl-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0214] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0215] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0216] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0217] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0218] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0219] The preparation of the PVDF conductive graphite substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0220] Embodiment 14:

[0221] A method for preparing a self-cleaning membrane using a two-dimensional lamellar structure, wherein the two-dimensional lamellar structure self-cleaning membrane is a ZnAl-MOFs membrane, zinc nitrate and aluminum nitrate are used with sodium hydroxide and sodium carbonate, and ZnAl-LDH is synthesized by coprecipitation and hydrothermal method, and then loaded on a PVDF conductive graphite substrate membrane, and then in situ converted into a 2DMOFs membrane by reacting with a terephthalic acid ligand. The specific synthesis route is as follows:

[0222] (1) Zn(NO3)2·6H2O (18 mmol) and Al(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0223] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0224] (3) Mix the above two solutions and stir vigorously for 1 h.

[0225] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0226] (5) After cooling, the solid ZnAl-LDH was thoroughly washed with deionized water and ethanol, and dried in an oven at 60°C for 12 hours.

[0227] (6) ZnAl-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0228] (7) The LDH solution was pumped onto the PVDF conductive graphite substrate membrane by vacuum filtration, and dried in an oven at 40° C. to constant weight to obtain an LDH membrane.

[0229] (8) Dissolve 150 mg of terephthalic acid in 60 ml of anhydrous ethanol, sonicate for 30 min, and transfer to a reactor.

[0230] (9) The LDH membrane of step (7) was placed in a reactor containing a terephthalic acid solution and reacted at 160° C. for 36 h to obtain a 2DMOFs membrane.

[0231] (10) After cooling, the 2D MOFs membrane was washed with ethanol several times and then dried in a vacuum at 60 °C to constant weight.

[0232] (11) Prepare 2D MOFs membranes with negatively charged surfaces.

[0233] The preparation of the PVDF conductive graphite substrate membrane is as follows: PVDF and polyvinyl pyrrolidone are dissolved in 50 ml of N,N-dimethylformamide (DMF) at a mass ratio of 7.54:1, and after being fully stirred for 24 hours, 50% conductive graphite powder in terms of organic high molecular weight is added and fully stirred at 60°C for 24 hours to obtain a casting solution; the casting solution is allowed to stand for 24 hours for degassing; the casting solution is cast and scraped on the surface of a non-woven fabric using a coating machine, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF conductive graphite substrate membrane with a thickness of 400 μm.

[0234] Embodiment 15:

[0235] Membrane fouling and electrocatalytic self-cleaning

[0236] (1) Bovine serum albumin (100 mg / L) was dissolved in water as a simulated pollutant. A membrane fouling experiment was conducted using an ultrafiltration cup nitrogen pressure device.

[0237] (2) The contaminated 2D MOFs membrane was bonded to a titanium mesh as an anode and a titanium sheet as a cathode and placed in a homemade self-cleaning device.

[0238] The titanium mesh and titanium sheet mentioned above were connected to a power source and electrocatalytic self-cleaning was performed at a constant current of 0.08 mA.

[0239] (3) Repeat steps (1) and (2) 3 to 5 times.

[0240] Embodiment 16:

[0241] Anti-fouling performance of membrane

[0242] (1) Bovine serum albumin (20 mg / L) was dissolved in water as a simulated pollutant. A membrane fouling experiment was conducted using an ultrafiltration cup nitrogen pressure device.

[0243] (2) 500 ml of BSA solution was filtered through PVDF membrane, CoFe-LDH membrane and CoFe-MOFs membrane, and the membrane pollutant water flux was measured.

[0244] (3) After the membrane is cleaned with 500 ml of pure water, its pure water flux is tested.

[0245] Comparative Example 1: Preparation of PVDF graphite substrate film

[0246] (1) Dissolve 7.54 g of polyvinylidene fluoride and 1 g of polyvinyl pyrrolidone in 50 ml of N,N-dimethylformamide and stir thoroughly for 48 h.

[0247] (2) Add 3.77 g of graphite to (1) and stir thoroughly for 24 hours to obtain a casting solution, which is then allowed to stand for 24 hours for degassing.

[0248] (3) A coating machine is used to cast a film on the surface of the non-woven fabric, and the film is placed in deionized water for phase inversion treatment to obtain a PVDF graphite substrate film.

[0249] Comparative Example 2: Preparation of CoFe-LDH membrane

[0250] (1) Co(NO3)2·6H2O (18 mmol) and Fe(NO3)3·9H2O (9 mmol) were dissolved in deionized water (30 mL) at a molar ratio of 2:1.

[0251] (2) Na2CO3 (24 mmol) and NaOH (57.6 mmol) were dissolved in deionized water (30 mL).

[0252] (3) Mix the above two solutions and stir vigorously for 1 h.

[0253] (4) The solution from step (3) was transferred to a stainless steel Teflon-lined autoclave and heated at 80°C for 48 h.

[0254] (5) After cooling, the solid was thoroughly washed with deionized water and ethanol, and the obtained CoFe-LDH solid was dried in an oven at 60°C for 12 hours.

[0255] (6) CoFe-LDH (75 mg) was added into ethanol solution (200 ml) and ultrasonicated for 30 min to fully disperse it.

[0256] (7) The LDH solution was pumped onto a PVDF membrane by vacuum filtration and dried in an oven at 40°C to constant weight.

[0257] 2. Test results

[0258] 2.1 Experimental setup

[0259] Experimental device: The experimental device of the present invention includes a dead-end ultrafiltration cup device, a peristaltic pump, and a flux test unit (PGC-1502, Adam, UK). The antibiotic concentration at the outlet was measured at a transmembrane pressure (TMP) of 0.2 bar and a flow rate of 6.25 ml / min.

[0260] 2.2 Test methods and results

[0261] 2.2.1 Test methods

[0262] The antibiotic concentration used in the test was 0.1125mmol / L. Samples were taken at 10, 20, 30, 60, and 120min to test the antibiotic removal concentration. The retention rate was calculated using the following equation: R = (C f -C p ) / C f ×100%, where C f and Cp are the concentrations of the feed solution and the permeate solution, respectively, and the concentrations of the solutions are measured by UV-Vis spectrophotometry. The membrane flux is calculated by connecting the nitrogen pressure device to the balance system.

[0263] 2.2.2 Results

[0264] (1) In order to explore the synthesis conditions of CoFe-LDH nanosheets, the CoFe-LDH nanosheets prepared by implementing Examples 1-3 are shown in Figure (1) under SEM electron microscope observation. The CoFe-LDH nanosheets of Example 3 exhibit the best nanolayered structure. The thickness of the nanosheets measured by AFM atomic force microscope in Figure (6) is about 0.77nm.

[0265] (2) In order to explore the dosage of CoFe-LDH, the 2D MOFs converted in situ by the CoFe-LDH membranes prepared in Examples 3-5 with different dosages intercepted antibiotics and other pollutants in the water under dead-end filtration conditions. The interception effect is shown in Table 1. The experimental results show that the best interception effect for antibiotics is 98.5% at a dosage of 75 mg CoFe-LDH nanosheets.

[0266] Table 1 The interception effect of different membranes on antibiotics in water

[0267] membrane Antibiotic retention rate (%) Example 3 98.5 Example 4 82.7 Example 5 65.8 Comparative Example 1 8.5 Comparative Example 2 70.37

[0268] The experimental results in Table 1 show that under the same conditions, the functional layer on the membrane has a certain interception effect on antibiotics due to the charge effect and the synergistic effect of the molecular sieve. When the dosage of LDH nanosheets is 75 mg, the in-situ converted CoFe-MOFs membrane has the best interception effect of 98.5% on antibiotics. Compared with the CoFe-LDH membrane converted in Comparative Example 2, the selectivity is increased by nearly 30%. It can be verified by Zeta potential test characterization that the surface potential of the 2D MOFs membrane after conversion is reduced from +23mV of CoFe-LDH to -8mV, and the membrane with negative charge on the surface has an electrostatic repulsion effect on pollutants such as negatively charged antibiotics.

[0269] (3) To explore the self-cleaning performance of the membrane, the self-cleaning performance of the membrane was explored by Example 13. Three cycle experiments were carried out as follows: Figure 8 As shown in the figure, after the membrane flux dropped by 50% in the first pollution cycle, the pollutants on the membrane were removed by the first powered self-cleaning method, and the membrane flux recovered to about 98.9% of the original value. After the second cycle, the membrane flux could still be restored to 97.3% of the original value. The powered self-cleaning method can effectively alleviate membrane pollution.

[0270] (4) The anti-fouling performance of the membrane was investigated. The anti-fouling performance of the membrane was investigated by Example 4. The results are as follows: Figure 7 As shown in (left), after filtering 500ml BSA solution, the membrane flux of PVDF membrane decreased by about 60%, and the membrane was seriously polluted. The CoFe-LDH membrane was second, with a membrane flux decrease of about 40%, which was better than the PVDF membrane in anti-pollution performance. This is because the surface of the CoFe-LDH membrane has a high hydrophilicity, with a contact angle of 23°. Since the contact angle of the CoFe-MOFs membrane is almost 0, it has good hydrophilicity. After filtering the BSA solution, it only decreased by 20%, showing excellent anti-pollution performance. By calculating its reversible and irreversible membrane pollution, such as Figure 7 As shown in (right), the CoFe-MOFs membrane has the smallest membrane resistance, and the proportion of reversible resistance is higher than that of the other two membranes.

[0271] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the specification and drawings of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a self-cleaning membrane using a two-dimensional sheet structure, characterized in that: The specific process conditions are: The first step is to prepare a conductive substrate membrane: dissolve an organic polymer and a porogen in 25-75 ml N,N-dimethylformamide DMF at a mass ratio of 7.54: 1-3, fully stir for 12-24 hours, add 50% conductive graphite powder based on the organic polymer molecular weight, and fully stir for 12-24 hours at 60-70°C to obtain a casting solution; let it stand for 12-24 hours to degas; use a coating machine to cast the casting solution on the surface of a non-woven fabric, place it in deionized water for phase inversion treatment, and obtain a PVDF conductive graphite substrate membrane with a membrane thickness of 200-400 μm; the organic polymer is polyvinylidene fluoride PVDF; Step 2, preparation of LDH: Solution A is prepared by dissolving divalent nitrate and trivalent nitrate in 30-60 mL of deionized water; then sodium hydroxide and sodium carbonate are dissolved in 30-60 mL of deionized water to prepare solution B; solution A and solution B are mixed and vigorously stirred for 1-2 hours, transferred to a stainless steel Teflon-lined autoclave for co-precipitation and heated at 80-120°C for hydrothermal reaction for 24-48 hours, cooled and washed thoroughly with deionized water and ethanol, and the obtained LDH solid corresponding to the metal is then dried in a vacuum at 60-70°C for 12-18 hours to prepare LDH nanosheets; the molar ratio of divalent nitrate, trivalent nitrate, sodium hydroxide and sodium carbonate is (1-2): (1-2): 6.4: 2.66; The third step is the preparation of LDH membrane: the LDH nanosheets are suspended in an ethanol solution, ultrasonicated for 30-60 min to be fully dispersed, vacuum filtered on a PVDF conductive graphite substrate membrane using an ultrafiltration cup, and then dried at 30-50°C for 6-12h to obtain the LDH membrane; Step 4, preparation of 2D MOFs membrane: by placing the LDH membrane in an anhydrous ethanol solution containing organic ligands, a 2D MOFs membrane is prepared by in-situ conversion on the membrane at 120-160°C for 24-48h, and after cooling, the 2D MOFs membrane is washed with ethanol several times, and then placed in a vacuum at 60-70°C for 12-18h to obtain a self-cleaning membrane using a two-dimensional lamellar structure; The organic ligand is one or more of terephthalic acid, 2,5-dihydroxyterephthalic acid and 2-aminoterephthalic acid; the preparation method of the anhydrous ethanol solution containing the organic ligand is to dissolve 50-150 mg of the organic ligand in 60 mL of anhydrous ethanol solution and ultrasonicate for 30 minutes.

2. The method for preparing a two-dimensional sheet structure self-cleaning membrane according to claim 1, characterized in that: In the first step, the porogen is polyvinyl pyrrolidone (PVP) and / or polyethylene glycol (PEG).

3. The method for preparing a self-cleaning membrane using a two-dimensional sheet structure according to claim 1, characterized in that: The divalent nitrate in the second step is one or more of cobalt nitrate Co(NO3)2·6H2O, zinc nitrate Zn(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and magnesium nitrate Mg(NO3)2·6H2O.

4. The method for preparing a self-cleaning membrane using a two-dimensional sheet structure according to claim 1, characterized in that: In the second step, the trivalent nitrate is ferric nitrate Fe(NO3)3·9H2O and / or aluminum nitrate Al(NO3)3·9H2O.

5. The method for preparing a self-cleaning membrane using a two-dimensional sheet structure according to claim 1, characterized in that: In the third step, the amount of LDH nanosheets used is 25-75 mg, the amount of ethanol solution used is 200 mL, the thickness of the functional layer of the filtered membrane is 5 μm, and the thickness of the functional layer of the 2D MOFs membrane after in-situ conversion by hydrothermal reaction in the fourth step is 15.6 μm.

6. An application of a two-dimensional sheet structure self-cleaning membrane prepared by any preparation method of claims 1-5 in high-throughput removal of PPCPs pollutants in sewage, characterized in that: The method of vacuum filtration is adopted, and the simulated pollutants on the membrane are degraded and removed in situ by using a two-dimensional sheet structure self-cleaning membrane as an anode under an external electric field. The pore size of the two-dimensional sheet structure self-cleaning membrane is 1-2 nm.

7. The use according to claim 6, characterized in that: The concentration of the simulated pollutant is 200 μg / L.

8. The use according to claim 6, characterized in that: The vacuum filtration is performed at a pressure of 0.1 - 5 bar.